How to Accept German Reparations - SUSAN SLYOMOVICS (University of Pennsylvania Press, 2014)
My par tic u lar family history illuminates justifi cations for and against reparations through discussions of indemnifi cation, the anthropology of â€œblood money,â€ guilt, and responsibility embedded in the ways these approaches both do and do not shed light on my motherâ€™s refusal to accept reparations for Auschwitz, in contrast to my maternal grandmotherâ€™s implacable pursuit of reparations from Germany, Hungary, and the Ukraine for over four de cades until her death in Israel in 1999 (Figure 2). My research project investigates aspects of histories and legal instruments of international human rights law relevant to remedies and specifi cally to a historical moment during which my family and their larger surrounding Jewish community aft er World War II were forced to confront the perils and possibilities of redress. Why do people pursue reparations? Th e eff ect of fi nancial indemnities as the primary form of reparation to survivors of torture and disappearance and the pursuit, or refusal, of reparation are part of a growing literature in human rights legal studies, with Holocaust survivors an obvious, much- studied group. When human rights violations are presented primarily through material terms for indemnifi cation, acknowledging an indemnity claim becomes one way for victims to be recognized. Remedy and redress are pro cesses that not only aff ord a vindication to the injured but also assume, or perhaps create, the existence of legal instruments with practical outcomes that determine what is to be done and how to rectify wrongs.